Developing Long Term Low Emissions and Climate Resilient Agricultural Development Pathways for Senegal: Getting ready for the LTS process - African Group of Negotiators Expert Support; Food and Agriculture Organization of the United Nations; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Senegal launched the process of developing its long-term, low carbon, climate resilient agricultural development pathway (Agriculture LTS) in May, 2021. The process is set to build on an existing long-term planning vision for climate agenda. The Agriculture LTS process is being coordinated by the Ministry of Environment and Sustainable Development (MEDD) in collaboration with the Ministry Agriculture and Rural Equipment (MAER).